DNA barcoding identified two endangered dolphins: threats on living aquatic mammals in India - Shantanu Kundu; Gopal Sharma; Srinivasan Balakrishnan; Kaomud Tyagi; Kailash Chandra; Vikas Kumar (Mitochondrial DNA. Part B. Resources, 2019)
DNA barcode data of both endangered dolphin species, Platanista gangetica, and Orcaella brevirostris are lacking in the global database. The study generated partial mitochondrial cytochrome c oxidase subunit I (mtCOI) gene sequences of the two highly threatened dolphin species from India. The family Platanistidae with one species and family Delphinidae with 12 species were showed 1.2%–19.7% between species genetic divergence in the studied dataset. Both P. gangetica and O. brevirostris were revealed distinct clade in neighbor-joining (NJ) phylogeny. Further, D. delphis, S. coeruleoalba, and T. truncatus have shown more than one clade and comparatively high genetic divergence within the species suggested prominent genetic variation between different populations. The study recommends generating more DNA barcode data from diverse habitats of P. gangetica and O. brevirostris to evaluate the exact population structure and adopting better conservation strategies thereafter.